Are We Global Yet? Progress on Expanding the Agricultural Communications Academic Discipline Internationally - Jefferson D. Miller (Journal of Applied Communications, 2025)
This commentary explores the agricultural communications discipline's evolution domestically in the U.S., leading to a discussion of the need for the academic discipline to expand internationally to countries where the profession is well established. To encourage early- and mid-career faculty to get involved in helping expand the discipline, descriptions of ongoing international programs are provided, featuring interviews with the faculty members who are leading them. Featured are programs led by faculty in agricultural communications programs at numerous institutions: Illinois (numerous countries); Florida (Canada); Texas Tech (Australia); Virginia Tech (Ghana); and Arkansas (United Kingdom). The commentary ends with a call to action, asking faculty to find solidarity in the effort to expand the discipline internationally.
Keywords: Academic Programs; International Education; Agricultural Commuincations